Microinterventional endocapsular nucleus disassembly for phacoemulsification‐free full‐thickness fragmentation. Issue 8 (August 2018) - Ianchulev, Tsontcho; Chang, David F.; Koo, Edward; MacDonald, Susan
Abstract : N/A: We describe a new technique for nucleus disassembly using a microinterventional approach. This is the first report of a microinterventional phacoemulsification‐free endocapsular lens fragmentation using a superelastic memory‐shaped nickel and titanium (nitinol) microfilament (miLOOP). After standard capsulorhexis and hydrodissection, the microinterventional loop is inserted through the 2.3 mm clear corneal incision. An actuation mechanism is used to unfold the microloop, which glides horizontally on the anterior surface of the lens, expands below the anterior capsule, and then rotates vertically while traveling in the hydrodissection plane to encircle the entire nucleus. Then, the loop is mechanically retracted within the sleeve, achieving full‐thickness centripetal segmentation of the nucleus. After rotation of the lens, the loop cuts can be repeated to create 4 or more segments without using phaco energy. The technique is independent of cataract grade and eliminates the need for phacoemulsification or femtosecond energy during the nucleus disassembly step of cataract surgery.